INVENTORY OF BRYOPHYTA DIVERSITY ON THE MADAPANGGA RIVER BIMA WEST NUSA TENGGARA INDONESIA - Risnawati, Risnawati; Bahktiar, Bahktiar; Herman, Herman (RUMPHIUS, 2023)
The diversity of mosses in the Madapangga river can be analyzed to find out their morphology and is rarely followed up by scientists as a small part of the flora that has not been explored much, and is also one of the supporting parts of flora diversity Ecologically, mosses play an important role in ecosystem function. Thus, the author aims to describe the moss in the madapangga river. Transect method and make a plot with a plot size of 10 x 10 m, starting from the south to ± 50 m towards the north with a rarity of 10 plots each and identification in the health department laboratory room, to calculate the diversity index of mosses (Bryophyta) using the formula shonner-winner (odum, 1993). the results of data analysis using the Shannon-winner formula while the overall value of the diversity index is H'= 0.636514 because the value is less than H < 1 then the species diversity is said to be very low. The species diversity is said to be very low if 1<H<3 then the species diversity is said to be moderate if H>3 then the diversity is very high.